2008
DOI: 10.1001/jama.299.7.785
|View full text |Cite
|
Sign up to set email alerts
|

Survival From In-Hospital Cardiac Arrest During Nights and Weekends

Abstract: HE INSTITUTE OF MEDICINE RE-ports that as many as 98 000 preventable in-hospital deaths occur annually. 1 Diagnostic, treatment, preventive, and other system errors have been identified as focus areas to prevent medical injury. 2 The detection and treatment of arrests and their antecedents may be less effective at night because of patient, event, hospital, staffing, and response factors. If in-hospital cardiac arrests are more common or survival is worse on nights and weekends, this information could have impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
313
10
15

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 515 publications
(359 citation statements)
references
References 22 publications
21
313
10
15
Order By: Relevance
“…24 We found a significant difference between initial rhythms for day and night time arrests with night time arrests having a higher number of initial non-shockable rhythms documented reflecting findings from other studies. 24 Our study has demonstrated that implementation of the ARC 2006 guidelines with an increased focus on minimally interrupted chest compressions has contributed to a trend towards improvement in survival to hospital discharge. Our results reflect other studies that examined the effect of implementing the amended guidelines.…”
Section: After Implementation Of the Arc 2006 Guidelines Our Results supporting
confidence: 86%
See 2 more Smart Citations
“…24 We found a significant difference between initial rhythms for day and night time arrests with night time arrests having a higher number of initial non-shockable rhythms documented reflecting findings from other studies. 24 Our study has demonstrated that implementation of the ARC 2006 guidelines with an increased focus on minimally interrupted chest compressions has contributed to a trend towards improvement in survival to hospital discharge. Our results reflect other studies that examined the effect of implementing the amended guidelines.…”
Section: After Implementation Of the Arc 2006 Guidelines Our Results supporting
confidence: 86%
“…17 Although our study identified age as a significant variable for survival to discharge it is considered a controversial prognostic factor. 18 Similar to our study previous research has shown that patients who arrest at night time have worse outcomes 20,23,24 and this is thought to be multi-factorial including differences in patients as well as health care staff, hospital staffing and operational factors. 24 We found a significant difference between initial rhythms for day and night time arrests with night time arrests having a higher number of initial non-shockable rhythms documented reflecting findings from other studies.…”
Section: After Implementation Of the Arc 2006 Guidelines Our Results supporting
confidence: 84%
See 1 more Smart Citation
“…To ensure that all cases in a hospital are captured, multiple case finding approaches are used including centralized collection of cardiac arrest flow sheets, review of hospital page system logs, and routine checks of code carts, pharmacy tracer drug records, and hospital billing charges for use of resuscitation medications. 13 The registry uses standardized Utstein-style definitions for defining clinical variables and outcomes. 14,15 Data completeness and accuracy is ensured by rigorous training and certification of hospital staff, use of standardized software with internal data checks and a periodic re-abstraction process.…”
Section: Data Source and Study Populationmentioning
confidence: 99%
“…[1][2][3] Nights and weekends are also associated with less aggressive care 4 higher rates of surgical complications 5 and medical errors, 6 and mortality from in-hospital cardiac arrest. 7 Factors cited as contributing to this disparity include skeleton medical and nursing coverage, often exacerbated by less experience, supervision, and patient familiarity than their weekday counterparts. 8,9 Limited specialized clinics, complex medical care, inter-professional expertise, and breakdowns in communication further compromise care during these times.…”
Section: Current Situationmentioning
confidence: 99%